Lead bioaccumulation in human breast cancer tissue is associated with DNA instability and cell death resistance - Manuel Scimeca; Erica Giacobbi; Rita Bonfiglio; Renata Sisto; Stefano Casciardi; Francesca Servadei; Daniel R. S. Middleton; Julia Bischof; Maria Paola Scioli; Giorgio Modesti; Eleonora Candi; Gerry Melino; et al. (Cell Death Discovery)
Abstract Lead (Pb) is increasingly recognized for its potential to alter cellular processes and contribute to cancer development. Although Pb is classified as a probable carcinogen by the IARC, the clinical evidence for its role in breast cancer is inconsistent and limited to epidemiological studies yet. The aim of this study was to investigate the Pb bioaccumulation in human breast cancer tissues by correlating its concentration with specific cancer factors related to carcinogenesis. Biopsy samples from 26 breast cancer patients were collected for molecular investigations (DNA and RNA sequencing), histological analysis, and the assessment of Pb concentration by ICP-MS. Data reported here revealed Pb bioaccumulation in all breast cancer samples, with a significant positive correlation between Pb levels and both Tumoral Mutational Burden and Microsatellite Instability, suggesting an association of Pb with genomic instability in human breast cancer samples. Additionally, Pb was associated with increased expression of cell death-related molecules such as BCL2 and p53. This association allows us to hypothesize a potential involvement of Pb in affecting cell death resistance. Interestingly, Pb concentration showed no correlation to other established prognostic and predictive biomarkers of breast cancer, such as PAM50. Thus, Pb concentration may represent a new independent risk factor for breast cancer development. This study provides new insights into the role of Pb bioaccumulation in breast cancer and suggests that environmental exposure to Pb may contribute to more aggressive tumor behavior through mechanisms involving genomic instability and resistance to apoptosis.